Le Paysage comme ressource dans les projets de développement territorial - Véronique Peyrache-Gadeau; Loïc Perron (Développement Durable et Territoires)
This article analyzes the landscape as a territorial resource. From the observation of two case studies in the French Alps: Beaufortain and Belledonne, we describe the social representations related to the landscape in a period where changes and new modalities of development are important. The notion of landscape resource is presented successively on a theoretical and descriptive point of view. It highlights the socio-economic situation of each of these contexts associated with a reflection on the identity and the future of these local societies